KEBERTERIMAAN KOSAKATA BAKU BAHASA INDONESIA OLEH MAHASISWA PRODI MANDARIN FKIP UNTAN - Nilam Ulfa Sani; Ahmad Rabi’ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to describe the attitudes of students of the FKIP UNTAN Mandarin Education Study Program towards standard Indonesian vocabulary. Especially through the acceptance of the sanding vocabulary. This is done to determine the choice of students and the reasons for choosing the vocabulary. The method used is descriptive method with qualitative research form. The data sources used in this study were 28 respondents. Fifty words and their equivalent forms were sampled. The results of this study indicate that both in terms of selection and use, several things can be concluded as follows. Vocabulary that is declared acceptable is described in 18 samples, vocabulary that is declared unacceptable is described in 16 samples, and vocabulary that is declared unacceptable is described in 16 samples. In determining the reason, respondents do not always make their choice based on linguistic rules, but respondents prefer based on their habit of using the word. This study is related to the 2013 curriculum in Indonesian Language Subjects in SMA class X semester I which is suggested as a Learning Implementation Plan (RPP) for teaching and learning activities in schools. Keywords: Acceptability, Standard, Vocabulary